Career construction and support of D/deaf high school learners in the Eastern Cape Province - Stemela, Unati (Division of Disability Studies, 2021)
D/deaf people typically are not employed, or work in menial jobs, although they have been through high1 school in the Eastern Cape Province of South Africa. The researcher has not observed them in professional careers. However, there is no empirical evidence why the D/deaf are excluded from the formal labour market after schooling. Understanding the underlying factors influencing such observations was important. The problem manifested in unemployment in the formal labour sector, but the researcher wanted to understand the root cause of this problem in depth. The aim of the study is to explore and critically analyse the D/deaf high school learners' construction of their careers and the supports available to them in constructing and realising their career aspirations. The international literature reviewed identifies knowledge gaps concerning career construction and supportive imperatives of D/deaf high school learners. The theory of career construction by Savickas (2005) frames this study and has been used throughout to guide and inform the study. This is a descriptive qualitative case study of career construction and support (Creswell, 2013). It was conducted in two of the five schools for the Deaf in two districts of the Eastern Cape. The learners came from rural, semi-rural and semi-urban homes. The schools (rural and semirural) were purposefully selected to participate in the study. The study population includes four participant groups; the deaf learners in high school (grade 10 -12), their parents, the teachers involved in the career guidance of the learners and members of the Department of Basic Education who were responsible for career guidance in deaf high schools. The data was collected using multiple methods: focus group discussions, individual interviews and document reviews. The findings indicate that careers are constructed under adverse conditions. These lead to learners' perceptions of limited support. The challenges with learning the school curriculum was a barrier to acquiring basic skills required for their careers. The challenges include an inability to use of South African Sign Language, a critical barrier affecting communication across participants (learners, teachers, Department of Education officials and parents). This impacted on teaching, learning, support, guidance and general communication. The contextual challenges and limited support structures negatively influence the way D/deaf high school learners in the Eastern Cape Province construct their future careers, their parents, the education system and the role played by organisations of Deaf people. The study shows that careers are constructed in a context of both positive and negative influences. The combination of both the negative influences and limited supports impacts more heavily on career construction than do the positive influences. D/deaf people in the Eastern Cape have limited opportunities to obtain employment in professional occupations because of the way the education system and society prepares them for such careers. The issues of colonialism and the previous apartheid regime still influence both the education system and the South African society.